THE INFLUENCE OF PROJECT EXTERNAL AND INTERNAL CONFLICT CONTROL ON PROJECT PERFORMANCE - Heru Bayuaji Sanggoro; Ladika Ladika (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
The data shows that many construction conflicts arise from many factors. Indonesia as a country that has social and cultural diversity is certainly very vulnerable to conflict, especially in project activities. Diversity as a necessity in the state has indeed contributed to the emergence of many social conflicts, including social conflicts in projects. This study aims to determine the control exercised by stakeholders in dealing with external and internal project conflicts that can have an impact on project performance. This study with a sample of 35 samples and using the SEM-PLS method. Based on the analysis, it shows a conclusion that conflicts that occur in projects, both internal conflicts, external conflicts and conflicts of interest, if not controlled properly, will have an impact on project performance. This is very necessary for stakeholders to be able to control conflicts that occur in the project.